Cellular expression profiles of Epstein-Barr virus-transformed B-lymphoblastoid cell lines - Arkom Chaiwongkot; Nakarin Kitkumthorn; Ratakorn Srisuttee; Supranee Buranapraditkun (My University, 2020)
Epstein-Barr virus (EBV) can infect human B cells and is associated with various types of B cell lymphomas. Studies on the global alterations of the cellular pathways mediated by EBV-induced B cell transformation are limited. In the present study, microarray analysis was performed following generation of two EBV-infected B-lymphoblastoid cell lines (BLCL), in which normal B cells obtained from two healthy Thai individuals and transcriptomic profiles were compared with their respective normal B cells. The two EBV-transformed BLCL datasets exhibited a high degree of similarity between their RNA expression profiles, whereas the two normal B-cell datasets did not exhibit the same degree of similarity in their RNA expression profiles. Differential gene expression analysis was performed, and the results showed that EBV infection was able to dysregulate several cellular pathways in the human B-cell genes involved in cancer and cell activation, such as the MAPK, WNT and PI3K-Akt signaling pathways, which were upregulated in the BLCL and were associated with increased cellular proliferation and immortalization of EBV-infected B cells. Expression of proteins located in the plasma membrane, which initiate a biological response to ligand binding, were also notably upregulated. Expression of genes involved in cell cycle control, the p53 signaling pathway and cellular senescence were downregulated. In conclusion, genes that were markedly upregulated by EBV included those involved in the acquisition of a tumorigenic phenotype of BLCL, which was positively correlated with several hallmarks of cancer.
Keywords: Lymphoblast; Viral-associated cancers and disorders